A Survey of Intrusion Detection System - Wanda P (University of Respati Yogyakarta, Indonesia, 2019)
Nowadays, the evolution of the internet and the use of computer systems has resulted in the huge electronic transformation of data that experienced multiple problems such as security, privacy, and confidentiality of information. Significant progress has been made in terms of improving computer systems security. However, security, privacy, and confidentiality of electronic systems are potentially major problems in computer systems. In this paper, we presented a survey on intrusion detection systems (IDS) in several areas. It consists of Web Application, Cloud Environment, Internet of Things (IoT), Mobile Ad-Hoc Network (MANET), Wireless Sensor Network (WSN) and Voice over Internet Protocol (VOIP)